Bibliometrics Analysis: Trend For Three Decades in Research Article of Web Module or Learning Module - Emia Erliasna (Journal of Computers for Science and Mathematics Learning, 2024)
This bibliometric analysis purpose is to find out how research has developed over the years. The aim of this research is to find out how the trend in publication of articles about web modules over the last 3 decades was developed. This article applied quantitative methods to develop and evaluate the bibliometric and vos viewer to mapping the relationship of variables. Bibliometric publications were retrieved from 1994 to 2023 from the scopus bibliographic database. Results: Articles published about web modules have increased over the past 3 decades. The determination value (R2) indicates that the exponential trend line is reliable. The most cited article is written by Happel, 1994 with 209. The most productive author is from Virginia Commonwealth University School of Medicine. The most productive country which published a paper around 1994 to 2023 is the United States with 1331 articles published. The most productive source for publishing articles is Archives of Physical Medicine and Rehabilitation with a total publishing of 161 articles. The top 1 institution is from China, with 63 articles published. From this article, it can be seen that the authors who conducted research on web modules are very diverse. There are no authors working together to write one article. The most frequently used keyword is “E-Learning” with a total of 211 appearances and total link strength 69.